ECONOMIC IMPACTS ON BRAZILIAN AGRIBUSINESS DUE TO NORTH AMERICAN FOREIGN POLICIES AGAINST IRAN AND THE USE OF LAWFARE IN THE INTERNATIONAL ECONOMIC WAR - Pires, Marcos Cordeiro [UNESP]; Ferreira Tamarindo, Ubirajara Garcia [UNESP] (Escola Superior Dom Helder Camara, 2021)
In an unprecedented diplomatic incident, in July 2019 the Islamic Republic of threatened to cut off all trade relations with Brazil if there was no supply of its ships, Bavand and Termeh, which were berthed at the port of Paranagua-PR, loaded with tons of Brazilian corn destined for export, and which were not supplied by Petrobras fearing economic sanctions by the United States, which would retaliate economically against the Iranians. In this context, although Brazil and Iran have no history of disputes, this episode demonstrated how the US foreign policy has the potential to harm the interests of Brazilian agribusiness, an economic sector that currently exports the most and generates a surplus in the country's balance of payments. , this article, conducted by a qualitative approach and bibliographic and documentary review, examined, from a diplomatic incident between Brazil and Iran, the geopolitical reasons for the conflict between Iranians and North Americans, and also how the The use of law fare, especially by the US Department of Justice and Federal Bureau of Investigation, as an instrument of foreign policy in the commercial and geopolitical war against countries, companies, international organizations and individuals, can collaterally impact the economic interests of Brazilian agribusiness.
Keywords: Brazilian agribusiness; economic sanctions; impacts; Iran; U.S